2015
DOI: 10.1097/md.0000000000002218
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Surgical Treatment for the Secondary Prevention of Stroke in Symptomatic Moyamoya Disease

Abstract: The treatment of moyamoya disease (MMD) is controversial and often depends on the doctor's experience. In addition, the choice of surgical procedure to treat MMD can differ in many ways. In this study, we performed a meta-analysis to determine whether surgical treatment of MMD is superior to conservative treatment and to provide evidence for the selection of an appropriate surgical treatment.The human case–control studies regarding the association of MMD treatment were systematically identified through online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 35 publications
0
52
1
2
Order By: Relevance
“…39 A recent meta-analysis investigating surgical outcomes of symptomatic MMD patients showed that perioperative complications were more frequent in the direct bypass group (30.2%) than in the indirect bypass group (18.8%), but the difference did not reach statistical significance (p = 0.176). 35 In our study, we did not see a significant difference in the overall postoperative complication rate when comparing the different surgical modalities.…”
Section: Figcontrasting
confidence: 46%
“…39 A recent meta-analysis investigating surgical outcomes of symptomatic MMD patients showed that perioperative complications were more frequent in the direct bypass group (30.2%) than in the indirect bypass group (18.8%), but the difference did not reach statistical significance (p = 0.176). 35 In our study, we did not see a significant difference in the overall postoperative complication rate when comparing the different surgical modalities.…”
Section: Figcontrasting
confidence: 46%
“…At present, accumulating evidence indicates that surgical revascularization may be the most effective treatment paradigm for ischemic MMD [37][38][39]. Our previous studies compared the long-term postoperative neurofunctional outcomes of different revascularization strategies and suggested that direct bypass was more effective in preventing recurrent ischemic strokes than indirect bypass for ischemic MMD, although neurological function outcomes were similar [40][41][42].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, two meta-analysis of the MMD treatment outcome have been published5154). Qian et al51) reported that bypass surgery significantly reduced future stroke than conservative treatment (OR 0.17; 95% CI : 0.12–0.26, p <0.01).…”
Section: Surgical Efficay In Symptomatic Adult MMD In Korea : a Meta-mentioning
confidence: 99%
“…Qian et al51) reported that bypass surgery significantly reduced future stroke than conservative treatment (OR 0.17; 95% CI : 0.12–0.26, p <0.01). But they did not find surgical benefit for MMD patients with ischemic presentation (OR, 0.45; 95% CI : 0.15–1.29, p =0.14).…”
Section: Surgical Efficay In Symptomatic Adult MMD In Korea : a Meta-mentioning
confidence: 99%
See 1 more Smart Citation